Modelling and optimization of a transit services with feeder bus and rail system / Mohammadhadi Almasi - Mohammadhadi, Almasi (2015)
many passengers use transit systems to reach their destination, while a growing concern for public transit is its inability to shift passenger‘s mode from private to public transportation. By designing a well-integrated public transit system and improving the cost-effectiveness network, public transport could play a crucial role in passenger satisfaction and reduce operating costs. The main objective of this research is to develop a mathematical formulation model for designing and coordinating schedules of integrated public transit services, which includes development of feeder services and coordination with major transportation services and transfer time consideration between two modes (i.e. Feeder bus and LRT). In the proposed improved model, the additional terms and constraints employed in objective function provide more accurate and efficient solutions for various conditions of transit systems, and this may lead to the creation of a more realistic model in simulating real-life problems. This is followed by application of the improved model to the benchmark and Petaling Jaya study areas. In this study, optimized transit services and coordinated schedules are developed using metaheuristic algorithms such as genetic algorithm (GA), particle swarm optimization (PSO), water cycle algorithm (WCA) and imperialist competitive algorithm (ICA). The data of the study were obtained based on the literature review, questionnaire survey and observation. Finally, obtained numerical results of the proposed model including optimal solution, statistical optimization results, the convergence rate as well as comparisons were discussed in detail. Therefore, optimum transit network was obtained by using ICA and WCA. As a result, the corresponding network costs obtained by PSO and GA are greater than ICA and WCA.